A randomised controlled pilot trial evaluating feasibility and acceptability of a computer-based tool to identify and reduce harmful and hazardous drinking among adolescents with alcohol-related presentations in Canadian pediatric emergency departments. Issue 8 (11th August 2017) - Newton, Amanda S; Dow, Nadia; Dong, Kathryn; Fitzpatrick, Eleanor; Cameron Wild, T; Johnson, David W; Ali, Samina; Colman, Ian; Rosychuk, Rhonda J
Abstract : Objective: This study piloted procedures and obtained data on intervention acceptability to determine the feasibility of a definitive randomised controlled trial (RCT) of the effectiveness of a computer-based brief intervention in the emergency department (ED). Design: Two-arm, multi-site, pilot RCT. Setting and participants: Adolescents aged 12–17 years presenting to three Canadian pediatric EDs from July 2010 to January 2013 for an alcohol-related complaint. Interventions: Standard medical care plus computer-based screening and personalised assessment feedback (experimental group) or standard care plus computer-based sham (control group). ED and research staff, and adolescents were blinded to allocation. Outcomes: Main: change in alcohol consumption from baseline to 1- and 3 months post-intervention. Secondary: recruitment and retention rates, intervention acceptability and feasibility, perception of group allocation among ED and research staff, and change in health and social services utilisation. Results: Of the 340 adolescents screened, 117 adolescents were eligible and 44 participated in the study (37.6% recruitment rate). Adolescents allocated to the intervention found it easy, quick and informative, but were divided on the credibility of the feedback provided (agreed it was credible: 44.4%, disagreed: 16.7%, unsure: 16.7%, no response: 22.2%). We found no evidence of a statistically significant relationship between which interventions adolescents were allocated to and which interventions staff thought they received. Alcohol consumption, and health and social services data were largely incomplete due to modest study retention rates of 47.7% and 40.9% at 1- and 3 months post-intervention, respectively. Conclusions: A computer-based intervention was acceptable to adolescents and delivery was feasible in the ED in terms of time to use and ease of use. However, adjustments are needed to the intervention to improve its credibility. A definitive RCT will be feasible if protocol adjustments are made to improve recruitment and retention rates; and increase the number of study sites and research staff. Trial registration: clinicaltrials.gov NCT01146665